PENERAPAN MODEL PEMBELAJARAN STAD SEBAGAI PERBAIKAN PRESTASI BELAJAR PKN SISWA DI KELAS IV SD NEGERI 027 HUBARA - Derhani Derhani (Jurnal Guru Kita PGSD, 2017)
Abstract: Application of Cooperative Learning Model of STAD as Improvement of Student Achievement Student PKN In Grade IV SDN 027 Huraba. Learning Civics in SDN 027 Huraba has not given a complete learning classical without remedial program. This condition is caused by the activity or active activities of students in learning is still low. It should be pursued learning which beroientasi on student activity (nurse at student) to improve student achievement.The research was conducted on the fourth grade students of SDN 027 Huraba with the number of 23 students. After the study lasted for two cycles can be concluded. Student activity data according to observer observation in cycle I are: reading / reading (52%), working (15,8%), asking fellow friend (12,9%), asking teacher (10%), and irrelevant KBM (10%) Student activity data according to observation in cycle II are: reading / reading (28%), working (23%), asking fellow friends (20%), asking teacher (13,0%), and not relevant to KBM (16.1%) Keywords: Improvement of Learning Achievement, Civics, Students, Learning ModelSTAD Abstrak : Penerapan Model Pembelajaran STAD Sebagai Perbaikan Prestasi Belajar PKN Siswa Di Kelas IV SDN 027 Huraba. Pembelajaran PKn di SDN 027 Huraba belum memberikan ketuntasan belajar klasikal tanpa program remedial. Kondisi ini disebabkan oleh aktivitas atau keterlibatan aktif siswa dalam pembelajaran masih rendah sehingga prestasi belajar siswa juga rendah. Perlu diupayakan pembelajaran yang beroientasi pada aktivitas siswa (berpusat pada siswa) untuk meningkatkan prestasi belajar siswa.Penelitian dilakukan pada siswa kelas IV SDN 027 Huraba dengan jumlah 23 siswa. Setelah penelitian berlangsung selama dua siklus dapat disimpulkan bahwa. Data aktivitas siswa menurut pengamatan pengamat pada siklus I antara lain:membaca/membaca(52%),bekerja (15,8% ), bertanya sesama teman (12,9%), bertanya kepada guru (10%), dan yang tidak relevandengan KBM (10%).Data aktivitas siswa menurut pengamatan pada siklusII antara lain: membaca/membaca (28%), bekerja (23%), bertanya sesama teman (20%), bertanya kepada guru (13,0%), dan yang tidak relevan dengan KBM (16,1%). Kata Kunci : Perbaikan Prestasi Belajar, PKn, Siswa, Model Pembelajaran STAD